Does Stress Increase Imitation of Drinking Behavior? An Experimental Study in a (Semi‐)Naturalistic Context. (1st October 2012) - Larsen, Helle; Engels, Rutger C. M. E.; Granic, Isabela; Huizink, Anja C.
Abstract : Background: That alcohol consumption is strongly influenced by the drinking behavior of social company has been demonstrated in observational research. However, not everyone is equally vulnerable to other people's drinking, and it is important to unravel which factors underlie these individual differences. This study focuses on the role of psychosocial stress in attempting to explain individual differences in the propensity to imitate alcohol consumption. Methods: With a 2 (confederate's drinking condition: alcohol vs. soda) × 2 (participant's stress condition: stress vs. no stress) experimental design, we tested whether the tendency to imitate other people's drinking was related to participants' induced stress levels. The young male adults ( N = 106) were randomly assigned to each of the conditions. In each session, directly after the stress or no‐stress period, confederates and participants entered a bar laboratory where we observed their drinking behavior. Prior to entering the session, confederates were instructed to drink alcohol or soda. Results: Participants in both stress and no‐stress conditions consumed substantially more alcohol when confederates drank alcohol than when they drank soda. There was no difference in alcohol consumed between stress and no‐stress conditions. No moderating effect of stress on the tendency to drink along with peers was found. Conclusions: Generally, it appears that among young male adults, imitation of alcohol consumption is a robust phenomenon not dependent on individual stress levels.